Spirituality and health : multidisciplinary explorations - Meier, Augustine, 1933-; O'Connor, Thomas St. James, 1950-; VanKatwyk, Peter L. (Peter Lorens), 1938- (Wilfred Laurier University Press, 2005)
Annotation